Multi-product firms, tariff liberalization, and product churning in Vietnamese manufacturing - Ha Thi Thanh Doan (Asian Development Bank Institute (ADBI), 2019)
Utilizing firm-level data covering the 2010-2015 period, this study documents the frequency and characteristics of multi-product firms in Vietnamese manufacturing. Our major findings are as follows. First, multi-product firms are larger, more capital-intensive, more productive, and are more likely to export. Second, multi-product firms are active in the market. Approximately 60% of firms adjust their product scope within a 6-year period. Third, the contribution of firms' product extensive margin to aggregate output growth is limited due to the prevalence of product dropping, which offsets the positive impact of product adding. Most output growth during the period is thus generated by the intensive margin. Turning to the link between tariff reduction and product shedding, we do not detect any significant impact. However, we find that exporters play an important role in product adding, which suggests that they may contribute to aggregate growth through the channeling of product scope expansion. Contrary to our expectations, our analysis offers limited support for the heterogeneity of product turnover across ownership types. While we find that state-owned enterprises are more likely to spread economic activities across products and industries, there is little difference in terms of product churning amongst foreign direct investment, state-owned enterprises, and the domestic private sector.
Keywords: F15; L23; 330; multi-product firms; trade liberalization